Enhancing the Understanding of Multicultural Islamic Education Values through the Study of Al-Hikam: The Role of Majelis Taklim - Zainul Arifin; Ahmad Marzuki; Saifulah Saifulah; Khimmataliev Dustnazar Omonovich (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2026)
Islamic teachings support harmonious social life in diverse communities. However, their internalization is often associated with formal education, while the role of nonformal institutions such as Majelis Taklim remains underexplored. One such forum is Majelis Taklim at Pondok Panggung, which regularly studies the classical Sufi text Al-Hikam by Ibn Ata Allah al-Sakandari. The teachings in this text emphasize moral refinement, spiritual awareness, and social harmony, making them relevant to multicultural Islamic education. This study aims to identify multicultural Islamic education values in the Al-Hikam and analyze the role of the Majelis Taklim in enhancing participants’ understanding of these values. This research employed a qualitative descriptive approach. Data were collected through observation, interviews with a religious teacher and congregation members, and documentation of learning activities, and these were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that the Al-Hikam contains key multicultural values, including tolerance (tasamuh), justice (al-‘adl), equality (al-musawah), peace (shulh), and brotherhood (ukhuwah). These values are conveyed through regular religious gatherings led by Manshur Bahruddin using contextual and accessible approaches. The Majelis Taklim functions not only as a space for religious learning but also as a medium for strengthening social interaction, solidarity, and mutual understanding among diverse community members.